CAN WORK ENGAGEMENT BE VİEWED FROM THE PERSPECTİVE OF ORGANİZATİONAL JUSTİCE? A RESEARCH ON ACADEMİCS (Third Sector Social Economic Review, 2023)
Work engagement, a concept that has attracted the attention of researchers in recent years, is considered as one of the key factors for organizational success. In this context, it can be said that determining the key factors that cause the emergence of work engagement behavior in employees is important for both academics and practitioners. Therefore, this study was conducted to find an answer to the question of whether organizational justice is an effective factor on work engagement in the context of Turkey. Within the scope of the research, data were collected from 399 academics working in state and foundation universities in Turkey and these data were analyzed. As a result of the analyses, it was understood that organizational justice perception positively affects work engagement with all its sub-dimensions, but this effect is at a low level. Accordingly, it is possible to say that more research should be conducted within the scope of the literature in order to determine the key factors that are effective in the emergence of work engagement behavior.
Keywords: Work Engagement; Vigor; Dedication; Absorption Organizational Justice